Review of State Administrative Law on the Implementation of the Complete Systematic Land Registration Program (PTSL) by the Land Office of Semarang Regency, Indonesia - Sari, Dwi Puspita; Syafa Marwah Febriyanti (HM Publisher, 2024)
Complete systematic land registration is a manifestation of the State's concern in the land sector, where it is responsible for fulfilling legal certainty for each property right holder. The program is held simultaneously throughout Indonesian territory and has its own objectives. The terminology of this PTSL realizes a form of perfection of the listing of the National Agrarian Operations (PRONA) project, where the stage of land certification is implemented on a massive and organized basis. The purpose of writing this article is to analyze the maintenance of the PTSL work program implemented by the land office of the district of Semarang. This research method uses normative research methods, which are qualitative descriptive and are derived from secondary data, namely data obtained through observations and interviews at the Land Office of Semarang Regency as well as from a variety of literature that comes from the article. By 2023, the City of Semarang, through the Land Office located in Semarang Regency, again became the target to obtain the target 26.139 fields of land that must be certified and has successfully completed as many as 17.629 certificates so that the percentage of performance with the presence of this PTSL program is 67.44 percent. The program has been conducted regularly and quite effectively, but it also raises some questions that still need to be addressed.